Hubungan Antara Tingkat Pengetahuan Ibu Hamil Multigravida Dengan Kepatuhan Kunjungan Antenatal Care Di Wilayah Kerja Puskesmas Kartasura - Kusumo, Bayu Argo; , Vinami Yulian, S.Kep, Ns.,M.Sc,Nursing (2016)
Maternal mortality/Angka Kematian Ibu (AKI) is a big problem in the field of health are mainly developing countries, such as in In donesia that is still classified as high when compared to other ASEAN countries. The cause of the AKI can be minimized by optimizing the efforts of Antenatal Care (ANC) the appropriate service standard on inspection of the pregnancy. ANC services aimed at preventing the occurrence of complications and disorders during pregnancy. Multigravida mother pregnancy examination is still as important as pregnancy before then are required to carry out the visit of the ANC so that the development of maternal and fetal condition of pregnancy can be tracked properly so it can suppress the number of morbidity and mortality in the mother and fetus. This research aimed to find the relationship between ultigravida knowledge, age of mother, age of the mother's pregnancy, parity and compliance in ANC. This study was descriptive correlative research and used cross sectional approach. This research was conducted in the area of Kartasura health center with multigravida population. Number of samples in the study consisted of 71 respondents. Sampling technique used total sampling. Data collection used questionnaire and books of maternal and child health/Kesehatan Ibu dan Anak (KIA). Data analysis used Spearman Rho. The result showed that, there is a relationship between the level of knowledge of multigravida pregnant women and compliance in antenatal care in the region (p-value = 0,044) conclusion.